Manajemen “KEPO” dalam Perawatan Diabetes Melitus Tipe 2 pada Keluarga Jawa dan Batak - Fitriani, Fitriani; Nasution, Siti Zahara; Bukit, Evi Karota (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of KEPO management in diabetes care on self-care and blood sugar levels of patients with DM in Javanese and Batak families. The method used was quasy experimental nonequivalent control group design. Respondents in this study were diabetics accompanied by one family member totaling 84 people. Data were collected using The Summary of Diabetes Self Care Activities (SDSCA) instrument and blood sugar level observation sheet (KGD). Data were analyzed by parametric T-test for self-care and non-parametric Wilcoxon and Mann Whitney for KGD. The results showed that there was a difference in the average self-care and blood sugar levels of patients with DM in Javanese and Batak families before and after being given KEPO management with a p-value = 0.001 (p <0.005). In conclusion, there is an effect of KEPO management on self-care and blood sugar levels of diabetics in Javanese and Batak families. Keywords: Diabetes Mellitus, Blood Sugar Levels, KEPO Management, Javanese Batak Families, Self-Care